Comparison of endoscopic papillary large balloon dilation with and without a prior endoscopic sphincterotomy for the treatment of patients with large and/or multiple common bile duct stones: a systematic review and meta-analysis - Liu P; Lin H; Chen Y; Wu Y; Tang M; Lai L (Dove Medical Press, 2019)
Pan Liu,1,* Huapeng Lin,2,* Yuanyuan Chen,3 Yu-Shen Wu,4 Maocai Tang,5 Liang Lai1 1Department of Hepatobiliary Surgery, The First People’s Hospital of Neijiang, Sichuan, People’s Republic of China; 2Department of Intensive Care Unit, Affiliated Hangzhou First People’s Hospital, Zhejiang University School of Medicine, Zhejiang, People’s Republic of China; 3Department of Oncology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 4Chongqing Key Laboratory of Molecular Oncology and Epigenetics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 5Department of Gastrointestinal Surgery, Chongqing University Cancer Hospital, Chongqing, People’s Republic of China *These authors contributed equally to this work Aim: To compare endoscopic papillary large balloon dilation (EPLBD) alone with EPLBD following endoscopic sphincterotomy (EST) in patients with large and/or multiple common bile duct stones.Methods: We conducted a comprehensive search of PubMed, EMBASE, and the Cochrane Library database to identify relevant available articles until July 19, 2018. Complete common bile duct stone (CBDS) removal rate, frequency of mechanical lithotripsy (ML) usage, total procedure time and intra- and postoperative adverse events were analyzed. We used RevMan 5.3 to perform the pooled analyses.Results: Seven RCTs matched the selection criteria. A total of 369 patients underwent EPLBD alone, and 367 patients underwent EPLBD following EST. Our meta-analysis revealed that there were no significant differences in terms of initial success rate (OR =0.69, 95% CI=0.44–1.09, P=0.11), frequency of ML usage (OR =1.18, 95% CI=0.68–2.05, P=0.55), rate of post-endoscopy pancreatitis (PEP) (OR =0.88, 95% CI=0.43–1.78, P=0.72), total procedure time (MD =1.52, 95% CI=-0.13–3.17, P=0.07), or other intra- and postoperative adverse events between the groups for patients with large and/or multiple CBDSs.Conclusions: EPLBD alone was comparable to EPLBD with prior EST in patients with large and/or multiple CBDSs. Further studies are required to confirm the mechanisms of PEP in patients who accept EPLBD during endoscopic retrograde cholangiopancreatography (ERCP). Keywords: endoscopic retrograde holangiopancreatography, ERCP, endoscopic papillary large balloon dilation, EPLBD, endoscopic sphincterotomy, EST, common bile duct stone, CBDS, meta-analysis